The Study and Analysis of The Prevailing Elements and Patterns in The Background of The Works of Mirzababa, A Qajar Painter - Keshtgar Ghasemi, Reihaneh; Asadi, Morteza (Journal of History Culture and Art Research, 2021)
The Qajar period is the beginning of many important and long-lasting developments in Iran's contemporary era. Among these developments, we should mention the changes in Iranian arts and the aspects that these arts had with them. Planning and backgrounding were among the aspects that entered Iranian painting with the entrance of Western art elements. Mirzababa was one of the most important painters of the first Qajar period, and the way he used these elements became an unwritten and frequently used pattern among artists. The purpose of the present article is to analyze the background of his works and to understand his backgrounding. The research is a theoretical and a descriptive-analytical research. The statistical population of the research consists of the works of Mirzababa and because the number of works that have reached us is limited, the sample size is all of his works. The research data show that Mirzababa had been backgrounding according to the type of art or used medium. Backgrounds have a general pattern or contractual elements that have an interior, exterior, or a combination of both spaces rather than the used medium.